2023
DOI: 10.1002/cb.2147
|View full text |Cite
|
Sign up to set email alerts
|

The impact of customer engagement on customer happiness

Abstract: Previous studies have found relationships between variables that predict happiness and engagement. While this suggests that engagement is a basis for generating customer happiness, the literature does not provide sufficient confirmatory evidence. Thus, the effects of different engagement intensities remain unclear. Focusing on conditions related to the Starbucks brand, this study analyzed how (1) passive and active engagement impacted customer happiness and (2) happiness impacted word of mouth (WOM) and purcha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 142 publications
0
5
0
Order By: Relevance
“…It means that the happiness derived from such consumption becomes synonymous with improvement in their social and personal quality of life (Ayadi et al, 2017). Secondly, this study demonstrates to the managers of these organizations that a greater understanding of consumer happiness and consumer brand management is the element that favors human beings' purchase intention in today's globalized society (Pipoli de Azambuja et al, 2023). It also highlights to marketing managers of fashion retail shops the need to undertake strategies focused on stimulating their consumers' hedonic and eudaimonic motivations, both at the time of purchase and in the postsale process (Ray and Nayak, 2023).…”
Section: Managerial Implicationsmentioning
confidence: 73%
See 3 more Smart Citations
“…It means that the happiness derived from such consumption becomes synonymous with improvement in their social and personal quality of life (Ayadi et al, 2017). Secondly, this study demonstrates to the managers of these organizations that a greater understanding of consumer happiness and consumer brand management is the element that favors human beings' purchase intention in today's globalized society (Pipoli de Azambuja et al, 2023). It also highlights to marketing managers of fashion retail shops the need to undertake strategies focused on stimulating their consumers' hedonic and eudaimonic motivations, both at the time of purchase and in the postsale process (Ray and Nayak, 2023).…”
Section: Managerial Implicationsmentioning
confidence: 73%
“…It means that the happiness derived from such consumption becomes synonymous with improvement in their social and personal quality of life (Ayadi et al ., 2017). Secondly, this study demonstrates to the managers of these organizations that a greater understanding of consumer happiness and consumer brand management is the element that favors human beings' purchase intention in today's globalized society (Pipoli de Azambuja et al. , 2023).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The analysis concluded that online reviews, etc., would have a positive impact on customer knowledge sharing [9]. Gina María Pipoli Azambuja, et al further investigated the relationship between passive and active customer engagement on customer well-being [10]. Lee, L. et al used an experience sampling method to explore the impact on customer-directed behavior using a customer-centered approach [11], while A. Gabaldón et al devised a customer demand baseline that can be used to assess response [12].…”
Section: Literature Reviewmentioning
confidence: 99%